ESTIMATION OF SEISMIC RESPONSE OF HISTORICAL AND MONUMENTAL SITES USING MICROTREMORS: A CASE STUDY IN THE ANCIENT APTERA, CHANIA, (GREECE) - Moisidi, M.; Vallianatos, F.; Makris, J.; Soupios, P.; Nikolintaga, M. I. (Bulletin of the Geological Society of Greece, 2004)
Main purpose of the present study is to investigate the dynamic characteristics of the remainings at the ancient city of Aptera (Chania) and identify the main damage mechanism, in order to evaluate the risk of structure damage or collapse in case of future events using microtremor recordings. Our study focuses on the application of HVSR method (Horizontal to Vertical Spectral Ratio) to microtremor measurements carried out in specific sites. Registrations have been performed by means of a tridirectional sensor Lennartz 3D-Lite (1 natural Hz frequency), connected with a 24-bit digital acquisition unit. A set of 10 time series of 800 second each, sampled at 125 Hz was recorded in several sites. The selected time windows of each time series were corrected for the base line and for anomalous trends, tapered with a cosine function to the first and last 5% of the signal, and band pass filtered from 0.5 to 20 Hz with cut off frequencies at 0.3 and 22 Hz. The same procedure performed for all sites and components and finally the H/V spectral ratios were computed. Most of the sites present significant amplification peaks in frequency around 2 Hz. Finally, electrical resistivity tomography was carried out. The extracted results clearly show a very complex subsurface geometry indicated by the presence of large-scale voids, which may possibly correspond to ancient reservoirs. In the present work we confirm that the archaeological site of Aptera in Chania consists of a very complex subsurface structure and that the results obtained by HVSR method and by resistivity method are very well correlated.